A Critical Assessment of the Swarnajayanti Gram Swarojagar Yojana (SGSY) in India - Sarkar, Susmita; Kumar, Mahesh (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
The present study is a critical assessment of Swarnajayanti Gram SwarojagarYojana (SGSY), a national level anti-poverty program of government of India with regard to poverty eradication and womens empowerment. Though SGSY scheme focuses only on poverty reduction and does not have explicit gender equality objectives, however more number of women members and women Self-help groups are encouraged to be linked with this program than men. The Ministry of Rural Development, Government of India, constituted a committee on credit related issues under SGSY to analyze the constraints in the adequate flow of credit to Self-help groups of SGSY and to suggest measures and strategies for promoting effective credit linkages to the SHGs and made two strategy of universalization coverage of SHGs assisted by bank credit and providing skills at least to one youth of a Below Poverty Line (BPL) family necessitates restructuring of SGSY.Â